2014
DOI: 10.1071/bt13223
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of flowering in spotted gum, Corymbia citriodora subsp. variegata and C. maculata

Abstract: Abstract. Genetically controlled asynchrony in anthesis is an effective barrier to gene flow between planted and native forests. We investigated the degree of genetically controlled variation in the timing of key floral developmental stages in a major plantation species in subtropical Australia, Corymbia citriodora subsp. variegata K.D. Hill and L.A.S Johnson, and its relative C. maculata K.D. Hill and L.A.S. Johnson. Flowering observations were made in a common garden planting at Bonalbo in northern New South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…There was however, no trend in northern provenances to flower earlier than the more southerly E grat provenances, a trend recorded for E. marginata 63 and for Corymbia citriodora subsp. variegata and C. maculata 27 . However, the opposite trend has been observed in E. globulus where Victorian provenances flowered later than the more southerly eastern-coast Tasmanian provenances 26 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There was however, no trend in northern provenances to flower earlier than the more southerly E grat provenances, a trend recorded for E. marginata 63 and for Corymbia citriodora subsp. variegata and C. maculata 27 . However, the opposite trend has been observed in E. globulus where Victorian provenances flowered later than the more southerly eastern-coast Tasmanian provenances 26 .…”
Section: Discussionmentioning
confidence: 97%
“…due to asynchrony in flowering time) may lead to unbalanced contributions of genetic material from individual parents to the next generation and reproductive isolation 23 . Several studies have shown that time of anthesis in eucalyptus is under genetic control, resulting in different flowering times between provenances and families 24 – 27 . Therefore, understanding the reproductive phenology of a seed orchard can enable culling reproductively isolated trees, families or provenances thereby increasing the overall level of outcrossing in the orchard.…”
Section: Introductionmentioning
confidence: 99%
“…Urban landscapes are often warmer than surrounding natural areas (Magee et al, 1999), and are maintained by human intervention, and thus can have increased soil moisture and soil nutrient loads (Sukopp, 2004;Neil and Wu, 2006). These factors have been hypothesized to promote more regular and intense flowering for plants, including locally indigenous Australian natives, within urban landscapes (e.g., Davis et al, 2016), although given the key role of photoperiod in regulating plant reproduction (Jackson and Thomas, 1999;Jarillo et al, 2008;Abasolo et al, 2014) it is unlikely that the season of flowering would change even if conditions were favorable. Thus, while urban landscape characteristics may promote more reliable flowering and extended food availability of locally indigenous plant species, it is unlikely that these locally indigenous species alone could support P. poliocephalus in Adelaide year-round.…”
Section: Discussionmentioning
confidence: 99%